(untitled) (American Journal of Society and Law, 2023)
Poverty is the most serious issue in the Philippines. The Philippine government’s response to the Millennium Development ans Sustainable Development Goals (?) of alleviating poverty worldwide is to provide cash assistance to Filipino households living below the poverty line. This financial assistance is an avenue for immediately responding to people’s needs, particularly in health and education; it is known as the Pantawid Pamilyang Pilipino Program or 4Ps in the Philippines. It aims to reduce poverty in the Philippines by investing in health and education, particularly for children aged 0 to 18. This research aims to assess the level of satisfaction of 4Ps beneficiaries with the cash grant they received from the government to cover their daily and other expenses. This research used the quantitative research design and the study was conducted in Nueva Ecija which covers 27 municipalities through an online survey. The researcher uses convenience sampling to identify the sample populating of Rao Soft calculator. The data collected from the locale were encoded, tallied, and analyzed. Statistical tools such as Percentage, Frequency Distribution, Weighted Mean, and Pearson R were used in analyzing the data gathered. According to the findings, beneficiaries are very satisfied with using their cash grants for educational purposes. It also shows that aside from education, food is the expense that the cash grants that were being misappropriated. Lastly, it is highly recommended that the beneficiaries be engaged in other worthwhile activities to be given by the local government unit for them to grow their money, so there would be no misappropriation in using the cash grants.